2008
DOI: 10.1111/j.1468-2982.2008.01574.x
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Skin Responses From Frontal Region in Migraine Headache: A Pilot Study

Abstract: Frontal sympathetic skin responses (F-SSRs) were recorded to investigate sympathetic nervous system activity in migraine headache (MH). Thirty-five patients with unilateral MH and 10 healthy volunteers were studied by evoking bilateral F-SSRs with electrical stimulation of the median nerve in attack, post-attack and interictal periods. The mean latencies were longer and the maximum amplitudes were smaller on the symptomatic side compared with the asymptomatic side (P < 0.05 for both amplitude and latency) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
(49 reference statements)
0
18
0
Order By: Relevance
“…If so, the question remains, whether observed asymmetry stems from the one-side prevalence or dysfunction of sympathetic or parasympathetic innervation. Previously, an asymmetry of autonomic regulation of blood flow in the face of migraineurs has been demonstrated by using infrared thermography [11], [12] and measurements of sympathetic skin responses [13] supporting the impairment of the sympathetic control in the face of migraine patients. Drummond explained the asymmetry by the activation of the trigeminovascular reflexes on the symptomatic side.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…If so, the question remains, whether observed asymmetry stems from the one-side prevalence or dysfunction of sympathetic or parasympathetic innervation. Previously, an asymmetry of autonomic regulation of blood flow in the face of migraineurs has been demonstrated by using infrared thermography [11], [12] and measurements of sympathetic skin responses [13] supporting the impairment of the sympathetic control in the face of migraine patients. Drummond explained the asymmetry by the activation of the trigeminovascular reflexes on the symptomatic side.…”
Section: Discussionmentioning
confidence: 84%
“…It was also reported that in the interictal period the pupil of the symptomatic side dilated more slowly and less extensively in the darkness than the opposite pupil, indicating an asymmetry of sympathetic outflow [12]. Asymmetry in the sympathetic skin responses was also found in the headache-free period in unilateral migraineurs [13], supporting the impairment of sympathetic control in the face. However, the relative phase of blood pulsations in the face of migraine patients has not been studied so far.…”
Section: Introductionmentioning
confidence: 83%
“…Recently, it has been shown that lipopolysaccharide‐induced inflammation increases after sympathetic denervation (Martelli et al, ). In a clinical study investigating sympathetic activity in different phases of migraine, sympathetic hypofunction was detected during the attack phase, and sympathetic hyperfunction was detected during the postattack phase (Yildiz et al, ). In a later study, measurements of salivary amylase levels were shown to support these results (Bugdayci et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Appelhans and Luecken 34 suggest that the HRV analysis could also be a reflection of the emotionality of the subjects. In cases of migraine, according to Yildiz et al, 35 there is an asymmetric sympathetic hypofunction on the symptomatic side in attack and interictal periods, whereas there is a hyperfunction in the postattack period. Thus, the hyperfunction of the sympathetic nervous system after a chiropractic adjustment, which could be similar to a postattack period of a migraine because the patient receives some relief could inhibit the HRV reaction and would seem to inhibit the parasympathetic reaction from the adjustment and a possible reaction that perhaps occurred in our pain-free group.…”
Section: Frequency Domain Analysismentioning
confidence: 96%